ENHANCING NUTRITIONAL VALUE: IRON –RICH CHIPS WITH MORINGA, MOCAF ANDMILKFISH FOR ANEMIA PREVENTION - Sutrisno Adi Prayitno; Sugiyati Ningrum; Silvy Novita Antrisna Putri (Agroindustrial Technology Journal, 2024)
The study aimed toproduce functional food products in the form of chips with sufficient iron (Fe) content and macronutrient content (carbohydrate, fat and protein content) which has the potential to prevent anaemia for girl’s teenager. This research used a Completely Randomized Design (CRD) method with three replications with several treatments including P1 as control (without moringa and milkfish, 100% wheat); P2 (1% moringa, 20% mocaf, 79% milkfish); P3 (3% moringa, 20% mocaf, 77% milkfish); and P4 (5% moringa, 20% mocaf, 75% milkfish). The resulting product was analyzed for iron (Fe) and macronutrient content such as carbohydrates, fat and protein. The data obtained was analyzed using SPSS for Windows version 25 software using a confidence level of 95% (α<5%) followed by a different test using DMRT (Duncan multiple range test). The results of ANOVA showed that a sig value <5% (0.000<0.05), showed that the substitute materials used have an influence on the levels of iron, protein, fat and carbohydrates. The iron in the product makes it possible to stimulate the prevention of anaemia in girl’s teenager. Besides, it was also supported by the presence of protein compounds on the substituted chips. The highest Fe value was 5.75 ppm, protein was 13.21%, fat was 5.21% and carbohydrates were 78.24%. Based on these parameters, P4 was the form of treatment that provides the best results, namely with a formulation of 5 grams of moringa, 20 grams of mocaf, and 75 grams of milkfish.